The effects of Acyclovir administration to NCI-H1975 non-small cell lung cancer cells. (March 2022) - Benedetti, Serena; Catalani, Simona; Canonico, Barbara; Nasoni, Maria Gemma; Luchetti, Francesca; Papa, Stefano; Potenza, Lucia; Palma, Francesco
Abstract: The biochemical mechanisms by which the antiviral drug Acyclovir (ACV) may induce anticancer effects even without detecting human herpesviruses (HHVs) are still poorly understood. Herein, we investigated for the first time how NCI-H1975 non-small cell lung cancer cells responded in vitro to ACV administration by exploring mitochondrial damage and apoptosis induction. We confirmed ACV ability to cause the inhibition of cancer cell growth even without detecting intracellular HHVs; the drug also significantly inhibited the colony formation capacity of NCI-H1975 cells. Cell cycle analysis revealed an increase of the sub-G1 hypodiploid peak after ACV treatment; the activation of caspase-3 and the presence of DNA laddering sustained the capacity of the drug to induce apoptotic cell death. Regarding mitochondrial toxicity, a reduction of mitochondrial membrane potential, altered mitochondrial size and shape, and mtDNA damage were found after ACV administration. Furthermore, an increment of intracellular reactive oxygen species levels as well as the upregulation of NudT3 involved in DNA repair mechanisms were observed. Altogether, these findings suggest that mitochondria may be possible initial targets and/or sites of ACV cytotoxicity within cancer cells in the absence of intracellular HHVs. Highlights: ACV caused NCI-H1975 cell growth inhibition. MMP reduction and altered mitochondrial size and shape were found. Molecular analysis revealed significant mtDNA damage upon ACV treatment. Mitochondria may be possible initial targets and/or sites of ACV cytotoxicity.